Lanthanide-Containing Light-Emitting Organic-Inorganic Hybrids: A Bet on the Future - Carlos, Luis D.; Ferreira, Rute A. S.; Bermudez, Veronica de Zea; Ribeiro, Sidney José Lima [UNESP] (Wiley-v C H Verlag Gmbh, 2009)
Interest in lanthanide-containing organic-inorganic hybrids has grown I considerably during the last decade, with the concomitant fabrication of materials with tunable attributes offering modulated properties. The potential of these materials relies on exploiting the synergy between the intrinsic characteristics of sol-gel derived hosts (highly controlled purity, versatile shaping and patterning, excellent optical quality, easy control of the refractive index, photosensitivity, encapsulation of large amounts of isolated emitting centers protected by the host) and the luminescence features of trivalent lanthanide ions (high luminescence quantum yield, narrow bandwidth, long-lived emission, large Stokes shifts, ligand-dependent luminescence sensitization). Promising applications may be envisaged, such as light-emitting devices, active waveguides in the visible and near-IR spectral regions, active coatings, and bio-medical actuators and sensors, opening up exciting directions in materials science and related technologies with significant implications in the integration, miniaturization, and multifunctionalization of devices. This review provides an overview of the latest advances in Ln(3+)-containing siloxane-based hybrids, with emphasis on the different possible synthetic strategies, photoluminescence features, empirical determination of the radiative and nonradiative transition rates, excited-state quantum efficiency, overall emission quantum yield and Omega(2,4,6) intensity parameters, and a quantitative description of host-to-Ln(3+) energy transfer processes. A summary includes future requirements, aims, and trends of this fascinating area, revising concurrently some of the main photonic applications.